PENINGKATAN KEMANDIRIAN ANAK SAAT MAKAN MELALUI KEGIATAN FUN COOKING MAKANAN KHAS TERNATE - Nurfitri Sahidun; Sukmawati Abdullah (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2020)
The aims of this research are to describes the process of implementation by the fun cooking of Ternate traditionally food activities and to analyzes the increasing of children autonomy in eating through fun cooking activities of Ternate traditionally foods. Respondents of the research involved of 12 children from group A at PAUD Titian Kasih. The method of this research consists: (a) plan, (b) action and observation, (c) reflection. The score of data from children autonomy in eating were analyzed by using quantitative and qualitative approach. The results shows that children could improve their autonomy in eating, they are like definite of choice when selection food or drink to consume, responsibility about the selection food or drink to consume, then doing something without helping from another people. Quantitative data shows that the children autonomy cycles have increased. Based on the data results shows in the end of the first cycle, it shows that children autonomy has increased about 10.37%, when pretest children autonomy has significantly 41,33 or 46,96%, therefore in the first cycle be 46 or 57,33%. The mean score in second cycle has significantly 64,47 or 79,92.